Tidal stream energy potential in the Shannon Estuary. (February 2022) - Fouz, D.M.; Carballo, R.; López, I.; Iglesias, G.
Abstract: The tidal and river in-stream energy resource in the Shannon Estuary (W Ireland) is investigated using of high-resolution numerical modelling and spatial analysis. Although freshwater discharges are large, their influence on the available resource is found to be all but negligible, the tide being the main driver of estuarine circulation. The Tidal Stream Exploitability (TSE) index is adapted to the analysis of estuaries with non-depth-limited areas (TSEndl ), such as the Shannon Estuary, and then used to select the hotspots with potential for a tidal stream farm. For this purpose, a new depth penalty-limiting function is defined to avoid overestimating the available energy potential in areas with depths greater than those required for tidal energy converter operation. Seven hotspots are identified based on the revised index. The approach followed in this study illustrates the applicability of high-resolution numerical modelling and spatial analysis for identifying the most appropriate areas for tidal stream energy conversion. Finally, the potential of tidal stream energy to contribute to the much-needed decarbonisation of the energy mix in Ireland is emphasized.